Complications of Radical Neck Surgery for Squamous Cell Carcinoma (Medical Forum Monthly, 2024)
Objective: To determine the complications of the Radical neck surgery for oral squamous cell carcinoma.Study Design: Cross-sectional Study.Place and Duration of Study: This study was conducted in Dental Section, Mayo Hospital, Lahore from 1ST January to 31ST December 2001.Materials and Methods: The study was conducted in dental section, Mayo hospital, Lahore. Fifteen patients of squamous cell carcinoma of the oral cavity were selected. All the patients underwent radical neck surgery. Postoperative complications were recorded at each follow up visit.Results: Post operatively, secondary hemorrhage occurred in 40.0%, of the patients, delayed healing due to infection in 73.3 % of the patients. There was no recurrence after 1 month, 3 month and 6 month. After 9 months recurrence was noted in 6.7% of patients.Conclusion: Complications occur after radical neck surgery. Recurrence however is lower with radical neck surgery.